2016
DOI: 10.5935/0103-5053.20160105
|View full text |Cite
|
Sign up to set email alerts
|

Review of Experimental GAPT and Infrared Atomic Charges in Molecules

Abstract: This review contains experimental values of polar tensors and generalized atomic polar tensor (GAPT) charges determined since the publication of the polar tensor formulism for infrared intensity interpretation in 1961. GAPT charges, also called mean dipole moment derivatives, for 167 atoms of 67 molecules are discussed and compared with infrared charges also determined completely from experimental intensities. The importance of the charge transfer and polarization dynamic contributions to the GAPT charge are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…It is worth mentioning that GAPT belongs to the select group of models that are accessible by both theory and experiment, and a compilation of experimentally determined GAPTs was published just a few years ago. 22 Two recent and very interesting contributions from Cho et al 15 and Manz 16 reported careful statistical analyses over more than 20 different schemes for computing atomic charges. Although aiming at different goals, they report similar results concerning the correlation between the various partition schemes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that GAPT belongs to the select group of models that are accessible by both theory and experiment, and a compilation of experimentally determined GAPTs was published just a few years ago. 22 Two recent and very interesting contributions from Cho et al 15 and Manz 16 reported careful statistical analyses over more than 20 different schemes for computing atomic charges. Although aiming at different goals, they report similar results concerning the correlation between the various partition schemes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since then, GAPTs have been used in hundreds of applications. It is worth mentioning that GAPT belongs to the select group of models that are accessible by both theory and experiment, and a compilation of experimentally determined GAPTs was published just a few years ago …”
Section: Introductionmentioning
confidence: 99%
“…The following numerical results were obtained using the same approach as in earlier studies on the CCTDP model; ,,,, the required inputs are the same. The geometry was optimized using Gaussian09, which also provided the raw IR frequencies and intensities and the Hessian matrix.…”
Section: Theorymentioning
confidence: 99%
“…Since then GAPTs have been used in hundreds of applications. It is worth mentioning that GAPT charges belong to the select group of charges accessible by both theory and experiment, and a compilation of experimentally determined GAPT charges was published just a few years ago [22].…”
Section: Introductionmentioning
confidence: 99%